Editorial: can quantitative fibrosis assessment be used to enhance prediction of outcomes in patients with alcohol‐related liver disease?. Issue 1 (17th December 2020) - Moodley, Prebashan; Dhanda, Ashwin D.
Abstract : LINKED CONTENT This article is linked to Israelsen et al papers. To view these articles, visit https://doi.org/10.1111/apt.16111 and https://doi.org/10.1111/apt.16150